Kolaborasi Guru BK dan Kepala Sekolah Dalam Supervisi Konseling Disekolah - M. Fahli Zatrahadi; Neviyarni Neviyarni; Riska Ahmad (Lembaga Riset dan Inovasi Almatani, 2022)
The purpose of this study is the collaboration of counseling and guidance teachers and school principals in supervising counseling in schools. This research uses an approach (library research). The object of research used is literature-based as study material. This strategy is used because there are still few who use it, it is very suitable for Indonesian conditions. The data used are as books, written documents and journal articles related to the research theme. Researchers used Nvivo software to help analyze data more accurately. The results showed that coaching carried the cooperation between the counseling and guidance teacher and the principal in the counseling supervision out and monitoring the counseling and guidance teacher. Here, it can be done by providing time opportunities during class hours so that counseling guidance teachers can improve their ability to provide counseling services in schools. The establishment of cooperation between guidance and counseling teachers and school principals as counseling supervision can achieve student development because counseling guidance teachers can interact directly with students and understand the needs of these students.